Long-Lasting Insecticide-Treated Nets: Assessment of the Awareness and Utilization of Them among Antenatal Clinic Attendees in Abakaliki, Southeast Nigeria - Chidebe Christian Anikwe; John Chiadikobi Irechukwu; Bartholomew Chukwunonye Okorochukwu; Cyril Chijioke Ikeoha; Johnson Akuma Obuna; Brown Nnamdi Ejikeme; Ifeyinwa Helen Anikwe (Journal of Tropical Medicine)
Background. The use of long-lasting insecticide-treated nets (LLITNs) is one of the effective strategies for the prevention of malaria, especially among pregnant women. Aim. This study is aimed at assessing the awareness and utilization of LLITNs during pregnancy among antenatal clinic attendees at the Alex Ekwueme Federal University Teaching Hospital Abakaliki. Materials and Methods. This was a cross-sectional study among antenatal attendees at the Alex Ekwueme Federal University Teaching Hospital Abakaliki, Ebonyi State. A semistructured questionnaire was used to obtain relevant information from the participants. Data analysis was done using SPSS version 20. Results. The mean age of the women was 26.05 ± 5.76 years. About one-third (30%) of the respondents were nulliparous. Most of the respondents had at least a secondary education. More than ninety percent of the respondents had a good knowledge of malaria with 95.8% being aware of LLITNs. The main source of information was from hospitals (54.5%). The rate of utilization of LLITNs was 37.5%; however, consistent use was only reported by about a third of this proportion. The major reasons for not utilizing the nets include discomfort/heat and fear of the chemical content. Women with tertiary education were more likely to utilize mosquito nets during pregnancy compared with women with secondary or primary education. Women who live in rural areas (OR = 0.393 95% CI 0.602–0.073) were less likely to use LLITNs during pregnancy, while those who are aware of the aetiology of malaria (OR = 4.38 95% CI 0.983–19.591) were more likely to utilize LLITNs in pregnancy. Conclusion. The level of awareness of LLITNs is high; however, its utilization was discouragingly low. Rural dwellers and those without appropriate knowledge of the aetiology of malaria were less likely to use LLITNs in pregnancy.